Corpo, beleza e gênero em imagens e nas falas das crianças na Educação Infantil: Entre a linha e o desalinho - JOROSKY, Narda Helena (2016)
This Master's thesis, linked to the Postgraduate Diploma in Education UNOESTE Program, presents research on the concepts of body and beauty, and their entanglements with gender relations as statements and expressions of boys and girls of four and five years members of an Infantile Education Institution in the city of Ribeirão Claro - Paraná. Bring the general objective: To identify and analyze the social and cultural mechanisms related to gender, in which produce the differences, hierarchies and subordination in relations between boys and girls. Among the specific objectives of this research are: Identify the expressed body images in visual artifacts present in materials in educational activities experienced by the children of early childhood education; Ascertain the lines on the body expressed by children and what criteria and cultural references are anchored their ideals for body beauty attributes of boys and girls; Investigate their conceptions of femininity and masculinity, from the reading they do the body images they are given to do; Analyze what are the meanings and judgments that children express for what is "beautiful body" and "ugly body" and what your links and / or implications in their gender representations. To achieve the results were perpassados problematizations paths that were about childhood, body, gender and visual culture based on dialogue with cultural studies and sociology of childhood. Besides the presentation of theoretical studies, this text spoke on the comments and dynamics made with the children during the search and his lines on the body, beauty, boy and girl. The methodology was based on historical-cultural studies and ethnography, so that the researcher was present in the context of the actions under consideration and kept a note attentive to details of spatial composition, its uses and the relationships that are established between the children in place. There were moments of interaction between the researcher and the children, and the application of a questionnaire for the parents and the use of semi-structured interviews for teachers and parents. I conclude this research by stating that children of very subtly escape adult power networks within the school environment, seeking to experience their bodies in different ways and experience different situations with its own rules, created within their children's cultural universes, ie , now on the line, now misaligning.